Feedback-Related Negativity and Frontal Midline Theta Reflect Dissociable Processing of Reinforcement - Rawls, Eric; Miskovic, Vladimir; Moody, Shannin N.; Lee, Yoojin; Shirtcliff, Elizabeth A.; Lamm, Connie (Frontiers in Human Neuroscience, 2020)
Prediction errors (PEs) encode representations of rewarding and aversive experiences, and are critical to reinforcement processing. The feedback-related negativity (FRN), a component of the event-related potential that is sensitive to valenced feedback, is believed to reflect PE signals. Reinforcement is also studied using frontal midline theta (FMΘ) activity, which peaks around the same time as the FRN and increases in response to unexpected events compared to expected events. We recorded EEG while participants completed a Monetary Incentive Delay task that included positive reinforcement and negative reinforcement conditions with multiple levels of outcome, as well as control conditions that had no reinforcement value. Despite overlap of FRN and FMΘ, these measures indexed dissociable cognitive processing. The FRN was sensitive to errors in both positive and negative reinforcement but not in control conditions, while frontal theta instead was sensitive to outcomes in positive reinforcement and control conditions, but not in negative reinforcement conditions. The FRN was sensitive to the point level of feedback in both positive and negative reinforcement, while FMΘ was not influenced by feedback point level. Results are consistent with recent results indicating that the FRN is influenced by unsigned PEs (i.e. a salience signal). In contrast, we suggest that our findings for frontal theta are consistent with hypotheses suggesting that the neural generators of FMΘ are sensitive to both negative cues and the need for control.